Aqueous broadband photopolymerization on microreactor arrays: from high throughput polymerization to fabricating artificial cells. Issue 7 (20th January 2022) - Zhou, Yue; Gu, Chuan; Zheng, Lifang; Shan, Fangjian; Chen, Gaojian
Abstract : Microreactor arrays combining ZnO and polyaniline are fabricated onto the bottom of multi-well plates to catalyze broadband sunlight-driven open-to-air polymerization in aqueous media. Abstract : Photopolymerization is attracting great attention due to its advantages, such as low cost and spatiotemporal control. Broadband photopolymerization is more attractive than ultraviolet polymerization, and is of special significance for better utilization of solar energy and has potential in biomedical applications. Herein, we report a facile and green approach to carry out broadband photopolymerization in aqueous media. Open-to-air sunlight polymerization (OSP) is catalyzed by microreactor arrays combining a semiconductor metal oxide (ZnO) and conductive polymer (polyaniline) fabricated via a breath figure patterning method. Controlled polymerization is realized and the green technology is demonstrated to be efficient in various applications, such as high throughput (HTP) polymerization and the synthesis of bioactive polymers inside artificial cells under simulated sunlight.